Attitude and awareness of the public toward genetic testing in Al-Madinah Al-Munawwara, Saudi Arabia - Alnefaie, Zayed; Makhlouta, Abdullatif; Alahmadi, Ghassan; Qumqumgi, Badr; Alhijili, Omar; Mufti, Faisal; Altamimi, Mohammad; Aloufi, Mohammed; Alkurdi, Abdullah A. (International Journal Of Community Medicine And Public Health, 2023)
Background: Genetic testing is a growing field that can provide valuable information about an individual’s health, ancestry, and potential risks for various health conditions. While some people are aware of its potential benefits, others have concerns about the privacy of their genetic data, limitations of the testing, ethical issues, and disparities in access to testing and interpretation services. While genetic testing has the potential to provide valuable information, there are valid concerns about privacy, accuracy, and ethical issues. The public’s attitudes toward genetic testing is shaped by various factors, including accessibility, cost, accuracy, and reliability of the testing and ethical and privacy concerns. A survey-based methodology was used to investigate the attitudes and awareness of the public toward genetic testing and identify the factors that influence these attitudes and awareness. Our study aimed to study the attitude and awareness of Saudi medical and non-medical students toward gene testing across different Universities in Al Madinah, Saudi Arabia. Methods: A cross-sectional study was conducted on 274 participants. The data were analyzed descriptively using statistical package for the social sciences (SPSS). Results: Across the 274 participants, the majority have agreed on the importance of gene studying especially in facilitating the marriage process and assuring healthier generations, while there was also a concern about the security and confidentiality of gene mapping and banking, screening for cancer, and cardiac disorder were on top of interest among the participants to use gene screening in. Conclusions: In conclusion, genetic testing is essential for diagnosing genetic diseases, but predictive genetic tests have limited benefits due to gene-environment interactions. Advances in genome technologies have produced large amounts of sensitive genetic data. Genetic education is necessary to promote informed decision-making, reduce genetic essentialism, and improve genomics literacy. Most study participants acknowledged the significance of genetic disorder screening before marriage to improve their health and their offspring’s health.